Abused but "Not Insulted": Understanding Intersectionality in Symbolic Violence in India. Issue 1 (April 2022) - Mukhopadhyay, Simantini; Chanda, Trisha
The fourth round of the Indian National Family Health Survey shows that the proportion of women who felt that wife-beating was justified exceeded the proportion of men who felt so in India. We find that more than one-fourth of the women in India who have experienced spousal bodily violence say that they never felt insulted by the action of their husbands. We hypothesise that this absence of the feeling of insult despite facing physical violence indicates the presence of symbolic violence. This form of violence manifests through symbolic channels and cannot take place without the complicity of the victim. Feminist writing in India has argued that gender needs to be considered at its intersection with class and caste to understand how the control of female sexuality relates to the organisation of production, sanctioned and legitimised by ideologies. We run instrumental variable probit regression of the likelihood of having felt insulted on the woman's economic class and social group affiliation. We find that once the experience of facing spousal physical violence and other background characteristics are controlled for, women from non-poor households are significantly less likely to have felt insulted, as compared to poor women. Furthermore, compared to women from most other social groups along the intersections of class and caste, non-poor upper caste women are less likely to report insult.